2016
DOI: 10.1016/j.pmedr.2016.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Associations between domains of physical activity, sitting time, and different measures of overweight and obesity

Abstract: ObjectiveTo describe 1) cross-sectional associations between domain-specific physical activity, sitting time and different measures of overweight/obesity and 2) longitudinal associations between patterns of change in physical activity and overweight/obesity ten years later.MethodsCross-sectional and longitudinal analyses based on the first and second follow-up of the Swiss cohort study SAPALDIA (SAP) were conducted (SAP2 in 2002/03, SAP3 in 2010/11). Physical activity was assessed by self-report using the long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
40
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(57 citation statements)
references
References 37 publications
15
40
0
2
Order By: Relevance
“…This finding concurs with recent reviews on the relationship of PA and obesity that suggested an absence of such a relationship [37,38]. Furthermore, work and domestic PA were not associated with obesity [39], supporting present findings. The commonly held position that increased physical activity is associated with a decrease in BMI [40,41] is in contrast with studies reporting positive associations between PA and BMI [15,16,42,43].…”
Section: Discussionsupporting
confidence: 93%
“…This finding concurs with recent reviews on the relationship of PA and obesity that suggested an absence of such a relationship [37,38]. Furthermore, work and domestic PA were not associated with obesity [39], supporting present findings. The commonly held position that increased physical activity is associated with a decrease in BMI [40,41] is in contrast with studies reporting positive associations between PA and BMI [15,16,42,43].…”
Section: Discussionsupporting
confidence: 93%
“…Our results agree with other cross‐sectional studies reporting a higher probability of obesity among those spending at least 4 hours in sitting position . Interestingly, a cross‐sectional assessment of the Swiss Cohort Study found that sitting time was directly related to per cent body fat assessed by bio‐impedance analysis, but not with BMI or WHR as in our results …”
Section: Discussionsupporting
confidence: 93%
“…However, there is still no consensus as to what level of body fat defines obesity in women or men. Recently, some researchers and fitness professionals used body fat of 32% as the cutoff for overweight/obesity in women , Wanner et al 2016. In other studies, the 35% body fat as a cutoff was used for obesity classification (Ilich et al 2015) and that of 33% and/or 38% showed adverse influence on various skeletal sites .…”
Section: :1mentioning
confidence: 99%
“…This is lower than the current cutoff for obesity being set at 40% body fat for women (Dufour et al 2013). As discussed above, different researchers used different levels for obesity classification in women, depending on the studied population and parameters examined (Ilich et al 2015, Wanner et al 2016. Moreover, Bosch and coworkers identified a cutoff of 38.3% body fat in women as an inflection point where the slope of the relation between visceral fat and percent body fat increases significantly (Bosch et al 2015).…”
Section: Interaction Among Aging Tissuesmentioning
confidence: 99%